The Visual Aspect of Translation Training in Multimodal Texts - Damaskinidis, George (Meta, 2016)
This paper explores the wider issue of translation training in multimodal contexts. The multimodal text represents a complex semiotic canvas on which the various systems of signification (verbal, images, colour, layout, etc.) interact in complex ways to produce a coherent meaning. Such interactions affect translation students’ understanding of multimodal texts and as such their training must also be visually-oriented in order to improve their translation efficiency when dealing with these texts. The paper is primarily (though not exclusively) concerned with the print multimodal text, and examines how the various aspects of the visual semiotic elements affect the teaching of its translation into another language. One such aspect is the new challenges that have been imposed by the visual on the field of translation studies. A second aspect is the visual implications for translation trainers and students. A third aspect is the wider multimodal context in which they have been found and involves the necessary multimodal approach to translation training, the development of a relevant awareness of multimodal texts and a number of other issues such as students’ creativity and the role of the subject specialist in the translation classroom. Finally, suggestions are made for further development of relevant teaching areas that are driven by the visual aspect of the multimodal text.